Dissemination of bacteria labeled with technetium-99m after laparotomy and abdominal insufflation with different CO2 pressures on rats - Pitombo,Marcos Bettini (2008)
PURPOSE: To asses the dissemination of bacteria labeled with technetium-99m (99mTc) from peritoneal cavity after different surgical procedures. METHODS: Bacteria of the Escherichia coli species labeled with 99mTc were used in a concentration of 10(8) units of colony-makers for ml (UFC/ml) and 1ml was inoculated through intra-peritoneal via. Forty-eight rats were divided into four groups: control, laparotomy, pneumoperitoneum with 10mmHg and pneumoperitoneum with 20mmHg of CO2. Procedures were performed 20 min after injection of the inoculum and lasted 30 min. Animals were sacrificed after six hours (Group 1) and 24 hours (Group 2). Samples of blood, liver and spleen were collected for radioactivity counting. RESULTS: After six hours, indirect detection of the bacteria in different organs was uniform in all groups. After 24 hours, a larger detection of technetium was observed in the livers of animals of the group insufflated with 20mmHg of CO2, when compared with those of control group (p<0.01). The other groups did not present statistically significant variations. CONCLUSIONS: The use of a higher intra-abdominal pressure was associated with a higher bacterial dissemination to the liver. The application of lower intra-abdominal pressures may be associated with a lower dissemination of the infectious status during laparoscopic approach of peritonitis status.